Understanding the high-temperature corrosion behavior of zirconium alloy as cladding tubes: a review - Tang, Yan; Liao, Jingjing; Yun, Di (Frontiers in Materials, 2024)
Operated under extreme conditions, corrosion occurs between zirconium alloy cladding tubes and the coolant in the primary loop of pressurized water reactors (PWRs), contributing to a reduction in the effective metallic material thickness. Therefore, understanding the corrosion behavior of zirconium alloy is vital to both raising the burnup of PWR and the improvement of safety properties of these reactors. During the past decades, extensive investigation was conducted with various conditions, such as changing corrosion temperatures and alloying elements, but contradiction persists and universal conclusions remain elusive. In the present work, a variety of research results that focused on corrosion kinetics, microstructural evolution, and the influence of alloying elements were integrated and summarized, so that a valuable reference can be provided to further research.